Infuence of chicken feather waste derived protein hydrolysate on the growth of tea plants under diferent application methods and fertilizer rates - Raguraj, Sriharan; Kasim, Susilawati; Md Jaafar, Noraini; Nazli, Muhamad Hazim (Springer, 2022)
Modern agriculture prioritizes eco-friendly and sustainable strategies to enhance crop growth and productivity. The utilization of protein hydrolysate extracted from chicken feather waste as a plant biostimulant paves the path to waste recycling. A greenhouse experiment was performed to evaluate the implications of different doses (0, 1, 2, and 3 g L−1) of chicken feather protein hydrolysate (CFPH), application method (soil and foliar), and fertilizer rate (50% and 100%) on the growth performance of tea nursery plants. The highest dose of CFPH (3 g L−1) increased the shoot and root dry weights by 43% and 70%, respectively over control. However, no significant differences were observed between 2 and 3 g L−1 doses in plant dry weight, biometric, and root morphological parameters. Foliar application of CFPH significantly increased all the growth parameters compared to soil drenching except N, P, and K concentrations in leaves and roots. Plants grown under 100% fertilizer rate showed better growth performance than 50% fertilizer rate. Tea nursery plants treated with foliar 2 g L−1 dose and grown under full fertilizer rate recorded the highest plant dry weight, root length, and root surface area. However, tea plants under 50% fertilizer rate and treated with foliar 2 and 3 g L−1 doses sustained the growth similar to untreated plants under 100% fertilizer rate. The significantly higher N, P, and K concentrations in leaves were observed in plants treated with soil drenching of 2 and 3 g L−1 CFPH doses under 100% fertilizer rate. Our results indicate that the application of CFPH as a foliar spray is highly effective in producing vigorous tea nursery plants suitable for field planting, eventually capable of withstanding stress and higher yield.